The effect of quality and how will it affect the performance / Farisya Rentah - Rentah, Farisya (2014)
The purpose of this study is to qualitatively discuss the professional musicians technique of quality practising. To be more in depth, this study aims to get the answer of the effect of quality practising and how will it affect the performance. The research is conducted by interviewing 2 principal piano major lecturers who have experience different type of performance from solo recitals to accompaniments and are still active in performing. The methodology for this full study involved 19 questions that were specifically focused on practising routine and performance issues. Besides ‘hat, a case study is prepared which is music by Sergei Prokofiev, Cinderella Waltz Op,102 No], in order for the respondents to elaborate more on their practising strategies. The finding from this research was analyzed and both of the respondents answers to the questionaire were compared to see the differences and similarities